Identification of the Effects of Chondroitin Sulfate on Inhibiting CDKs in Colorectal Cancer Based on Bioinformatic Analysis and Experimental Validation - Zhou, Yingyu; Li, Xuyang; Morita, Yuki; Hachimura, Satoshi; Miyakawa, Takuya; Takahashi, Sachiko; Tanokura, Masaru (Frontiers in Oncology, 2021)
With a high occurrence rate and high mortality, the treatment of colorectal cancer (CRC) is increasingly attracting the attention of scholars. Hub genes that determine the phenotypes of CRC become essential for targeted therapy. In the present study, the importance of cyclin-dependent kinases (CDKs) on the occurrence of CRC was identified by data mining of The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). The results showed that the gene expression levels of CDK1, CDK4, and CDK6 were obviously changed in different stages of CRC. Among the CDKs, CDK4 was suggested as an independent risk factor for CRC based on Cox analysis. Furthermore, chondroitin sulfate (CS), a kind of dietary supplement to treat osteoarthritis, was predicted to treat CRC based on its chemical structure and GEO datasets. Cell assay experiments with the human CRC cell line HCT-116 also verified this prediction. CS inhibited the gene and protein expression levels of CDKs and increased the ratios of apoptotic or dead HCT-116 cells by regulating mitogen-activated protein (MAP) kinase pathways. Our data highlight the essential roles of CDKs in CRC carcinogenesis and the effects of CS on treating CRC, both of which will contribute to the future CRC treatment.